A divulgação de informações sobre obras públicas no município de Vitória à luz da teoria da transparência e da accountability - Duarte, Marcell Gomes (2024)
This study analyzed the disclosure of information on public works in the municipality of Vitória/ES during the period from 2020 to 2022, based on the theories of transparency and accountability. The research developed a methodological approach grounded in content analysis, utilizing a proprietary evaluation scale encompassing six main categories: project progress, disclosure of financial data, access to documents, promotion of citizen participation, budgetary information, and asset information. Data were collected through the Transparency Portal of the Vitória City Hall, Management Reports, and the Control Panel of the Espírito Santo State Court of Auditors. The results showed significant improvement in four categories: I – Justifications for changes in works (score increased from 2 to 3), II III – Frequent updates (score increased from 3 to 4),– Availability of financial reports (score increased from 4 to 5), and IV – Detail of budgetary information (score increased from 3 to 4). The analysis of financial statements revealed a 33.3% growth in fixed assets, reflecting investments in infrastructure. However, a deterioration in the quality of asset information was identified, with a score reduction from 3 to 2. As a technical product, a practical guide was developed on essential content for public works information disclosure, establishing evaluation indicators for municipal institutional websites. It is concluded that, although the municipality has made progress in various areas of transparency, challenges remain, particularly in the management and disclosure of asset information related to infrastructure works.